Readiness of Parents of Students Against Vaccination During the Covid 19 Pandemic - Irfan Dahnial; Ismail Saleh Nasution; M Fauzi Hasibuan (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The vaccination program is expected to bring back a broad positive impact on society, namely social and economic productivity. However, to successfully implement this COVID-19 vaccination plan, at least three key factors are required, namely the COVID-19 vaccine (including its provision and use); health workers; and community involvement. For a COVID-19 vaccination plan to be successful, these three factors must be defined and integrated. Research on the new corona virus vaccine is one of the stages of providing vaccines, so almost all countries are competing for this vaccine research. Research and discovery of a COVID-19 vaccine has been very rapid, including the reason for its wide impact, but also because it is supported by very modern research techniques and a huge budget that the world has never seen before.